High temperature resistant polymer systems - Sek, Soon Ann. (2011)
In this work, graphite/resorcinol-based pthalonitrile (GH/RPh) composite foams were fabricated. Three different parameters, probe sonication duration, loading and different graphite treatment methods were investigated. At the mass fraction of 0.10, the storage modulus and the Tg was 412.97 MPa and 307.48 oC respectively. In addition the loading of graphite had also increase the thermal stability of composite. At a mass fraction of 0.10, the char yield at 800oC was 66.80%. However, the compression stresses of the foams decreases with increasing loading of graphite. The results indicated that probe sonication duration had a minimal effect on the properties, while different treatment display a mixture of trends. Hence this suggests that, on top of the dispersion of graphite, interaction of the graphite with polymer matrix plays a role in determining the properties.